Policies to strengthen the resilience of global value chains Empirical evidence from the COVID-19 shock - Schwellnus, Cyrille (OECD Publishing, 2023)
Widespread supply disruptions in the wake of the COVID-19 pandemic and the Russian Federation's large-scale aggression against Ukraine have raised concerns among policy makers that globalised value chains expose domestic production to shocks from abroad. This paper uses new indicators of global value chain dependencies and exogenous pandemic shocks to econometrically estimate the effects of supply disruptions abroad on domestic output. The results suggest that the adverse effects of supply disruptions are particularly large when concentration of supplying countries and supplying firms is high. Counterfactual simulations of the econometric model suggest that diversification of suppliers would have sizeable benefits in terms of shielding domestic production against country-specific supply shocks, with partial onshoring of production having only small additional benefits. Technological innovation that reduces foreign dependencies, such as the substitution of renewable energies for fossil fuels, can have similar benefits as diversification
Keywords: Science and Technology; Economics; Trade; Industry and Services